Telehealth for Substance Use Disorders: A Rapid Review for the 2021 U.S. Department of Veterans Affairs and U.S. Department of Defense Guidelines for Management of Substance Use Disorders - Uhl, Stacey; Bloschichak, Aaron; Moran, Amber; McShea, Kristina; Nunemaker, Megan S; McKay, James R; D'Anci, Kristen E (Annals of internal medicine, 2022)
Approximately 20.4 million Americans met criteria for a substance use disorder (SUD) in 2019; however, only about 12.2% of persons with an SUD receive specialty care. Telehealth offers alternatives to traditional forms of substance use treatment. To synthesize recent findings on the efficacy of telehealth for SUDs. MEDLINE, Embase, PubMed, and the Cochrane Library from January 2015 through August 2021 (English language only). Randomized controlled trials (RCTs) of adults with a diagnosis of SUD based on the or International Classification of Diseases. One investigator abstracted data and assessed study quality, and a second checked for accuracy. This rapid review synthesized evidence from 17 RCTs. Evidence is very uncertain that telehealth provided as videoconference therapy (1 RCT) or web-based cognitive behavioral therapy (CBT) (3 RCTs) has similar effects to in-person therapy for improving abstinence from alcohol or cannabis. Low-strength evidence suggests that web-based CBT has similar effects for improving abstinence in multiple SUDs (2 RCTs). Low-strength evidence suggests that adding supportive text messaging to follow-up care improves abstinence and amount of alcohol per day (2 RCTs) but does not improve emergency department visits or frequency of consumption (2 RCTs). Enhanced telephone monitoring likely reduces readmissions for SUD detoxification compared with usual follow-up alone (1 RCT) but does not reduce days of substance use (low-strength evidence). Narrative synthesis, heterogeneity of telehealth interventions, no assessment of publication bias, and study methodology. Evidence is very uncertain that telehealth is similar to in-person care for SUD outcomes. Limited evidence suggests some benefit of adding telehealth to usual SUD care. U.S. Department of Veterans Affairs Veterans Health Administration.